2005
DOI: 10.1677/erc.1.00719
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases-1 in breast cancer

Abstract: Whether patients diagnosed with primary breast cancer are offered adjuvant systemic therapy following surgical removal of the tumor is based on prognosis. Prognosis is estimated in every patient using established prognostic variables. Unfortunately, when using the currently available prognostic parameters a significant proportion of patients are over-treated. Thus, in order to improve stratification of breast cancer patients, additional prognostic factors need to be identified. Tissue inhibitor of metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 69 publications
(58 reference statements)
4
69
0
Order By: Relevance
“…Furthermore, by cleaving proapoptotic factors, MMPs produce a more aggressive phenotype via generation of apoptotic resistant cells [20]. MMPs also regulate cancer-related angiogenesis, positively through their ability to mobilize or activate proangiogenic factors [21], and negatively via generation of angiogenesis inhibitors, such as angiostatin and endostatin, cleaved from large protein precursors [22] On the other hand, it is now accepted that TIMPs are multifactorial proteins also involved in the induction of proliferation and the inhibition of apoptosis [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by cleaving proapoptotic factors, MMPs produce a more aggressive phenotype via generation of apoptotic resistant cells [20]. MMPs also regulate cancer-related angiogenesis, positively through their ability to mobilize or activate proangiogenic factors [21], and negatively via generation of angiogenesis inhibitors, such as angiostatin and endostatin, cleaved from large protein precursors [22] On the other hand, it is now accepted that TIMPs are multifactorial proteins also involved in the induction of proliferation and the inhibition of apoptosis [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinases may also regulate cancer/related angiogenesis, both positively through their ability to mobilise or activate proangiogenic factors (Stetler-Stevenson, 1999) and negatively via generation of angiogenesis inhibitors, such as angiostatin and endostatin, cleaved from large protein precursors (Cornelius et al, 1998). In addition, it is now assumed that TIMPs are multifactorial proteins also involved in the induction of proliferation and the inhibition of apoptosis (Jiang et al, 2002;Wurtz et al, 2005).…”
mentioning
confidence: 99%
“…Currently, four different TIMPs are known to exist: TIMPs 1, 2, 3 and 4. However, it is now assumed that TIMPs are multifactorial proteins that are also involved in the induction of proliferation and inhibition of apoptosis (Wurtz et al, 2005).The expression in prostate cancer of several MMPs and TIMPs, such as MMP-2, -7, -9, -13 and -14, TIMP-1, -2 and -3, has been recently reported ( The objectives of this study were to evaluate the expression and clinical relevance of several MMPs and TIMPs of previously recognised biological importance in prostate carcinomas, using the tissue array (TA) technique. This technique has allowed us the processing of a large number of tissue specimens for a wide range of protein determinations.…”
mentioning
confidence: 99%
“…If TIMPs inhibit MMPs in vivo, it should be expected that high levels of these inhibitors would prevent tumour progression and thus be related with low aggressiveness of tumours. However, TIMPs are multifunctional proteins that, in addition to its MMP-inhibitory effect, also show distinct tumourstimulatory functions involved in the induction of proliferation and inhibition of apoptosis (Jiang et al, 2002;Wurtz et al, 2005).In this study, we also investigated the possible relationship between each one of MMPs or TIMPs expressions and clinical outcome, such as PSA-defined recurrence after radical prostatectomy in our studied population. Our results showed that the global expression of MMP-11 and -13 by prostate carcinomas correlated with higher incidence rate of biochemical relapse.…”
mentioning
confidence: 99%